Mutation detection in formalin-fixed prostate cancer biopsies taken at the time of diagnosis using next-generation DNA sequencing. Issue 3 (13th January 2015) - Manson-Bahr, David; Ball, Richard; Gundem, Gunes; Sethia, Krishna; Mills, Robert; Rochester, Mark; Goody, Victoria; Anderson, Elizabeth; O'Meara, Sarah; Flather, Marcus; Keeling, Matthew; Yazbek-Hanna, Marcelino; et al.
Abstract : Aims: Assessing whether next-generation DNA sequencing (NGS) can be used to screen prostate cancer for multiple gene alterations in men routinely diagnosed with this disease and/or who are entered into clinical trials. Previous studies are limited and have reported only low success rates. Methods: We marked areas of cancer on H&E-stained sections from formalin-fixed needle biopsies, and used these as templates to dissect cancer-rich tissue from adjacent unstained sections. DNA was prepared using a Qiagen protocol modified to maximise DNA yield. The DNA was screened simultaneously for mutations in 365 cancer-related genes using an Illumina HiSeq 2000 NGS platform. Results: From 63 prostate cancers examined, 59 (94%) of the samples yielded at least 30 ng of DNA, the minimum amount of DNA considered suitable for NGS analysis. Patients in the D'Amico high-risk group yielded an average of 1033 ng, intermediate-risk patients 401 ng, and low-risk patients 97 ng. NGS of eight samples selected from high-risk and intermediate-risk groups gave a median exon read depth of 962 and detected TMPRRS2-ERG fusions, as well as a variety of mutations including those in the SPOP, TP53, ATM, MEN1, NBPF10, NCOR2, PIK3CB and MAP2K5 (MEK5) genes. Conclusions: Using the methods presented here, NGS technologies can be used to screen a high proportion of patients with prostate cancer for mutations in cancer-related genes in tissue samples opening up its general use in the context of clinical trials or routine diagnosis.